Combination of a poly(3, 4-ethylene-dioxythiophene) electrode in the presence of sodium dodecyl sulfate with centri-voltammetry. Issue 16 (21st August 2015) - Tepeli, Yudum; Aslan, Sema; Sezer, Esma; Anik, Ulku
<x xml:space="preserve">Abstract</x> A poly(3, 4-ethylene-dioxythiophene) (PEDOT) electrode was prepared by electropolymerization of 3, 4-ethylene-dioxythiophene in the presence of sodium dodecyl sulfate (SDS). Then this electrode was combined with centri-voltammetry for the first time and applied for dopamine (DA) detection.